WEB-BASED LANGUAGE CLUB AFFECTING EFL LEARNERS' PROFICIENCY: A CASE OF IRANIAN LEARNERS - Hamid Ashraf; Maryam Salami (University of Kuningan, 2014)
Abstract: Language clubs have been reported to be effective in learning languages, increasing motivation and independence (Gao, 2009). The present study was an attempt to investigate the effect of a web-based language club on the language proficiency of Iranian EFL learners. A number of pre-intermediate learners form two universities (118) were selected among 154 through a test of proficiency (TOEFL PBL), then they were put into experimental and control groups. The participants in experimental group got on line and acted as a member of a virtual language club for a period of 6 months. They got involved with activities like emailing, chatting, and weblogging. Data were collected through TOEFL PBL. The analyzed data from the test of proficiency indicated the outperformance of those in experimental group. Consequently, it might be proposed that web-based language clubs can make language learning easier and more efficient. Keywords: Web-based language club, English Proficiency, EFL learners